Implementation of Sexual Violence Criminal Resolution by Pidie District Police in Building a Sense of Justice - Setyadi, Rangga; Prianggono, Jarot; Halimah; Safii, Mifta Hadi (Dinasti Research, 2025)
This study aims to describe the implementation of sexual violence crime resolution by the Pidie District Police in building a sense of justice and to identify the factors hindering the resolution of sexual violence cases by the Pidie District Police. The theoretical framework used for analysis includes Performance Theory, Law Enforcement Theory, and the Concept of Sexual Violence. This research employs a qualitative approach with a descriptive research method. Primary data is collected through interviews and observations, while secondary data is obtained through documentation studies. The data analysis techniques in this research include data reduction, data presentation, and data verification. The research approach focuses on the handling of sexual violence crimes at the Pidie District Police, showing a significant increase in cases between 2023 and 2024. The Women and Children Protection Unit (PPA) at Pidie District Police plays a crucial role in enforcing the law and protecting victims through a professional criminal justice system, involving various related institutions. However, challenges such as limited human resources, facilities, threats to victims, and social stigma against victims remain significant obstacles. Efforts to enhance personnel capacity, facilitate victim recovery, and strengthen cooperation with the community and relevant institutions are needed to improve the effectiveness of case handling. The Pidie District Police continues to enhance training and capacity building for personnel in the Women and Children Protection Unit (PPA) to address challenges in handling sexual violence cases, focusing on improving skills in victim conducting-sensitive investigations and strengthening inter-institutional coordination to provide more effective protection for victims.